2016
DOI: 10.1007/s11882-015-0581-6
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Group 2 Innate Lymphoid Cells in Human Airway Disease

Abstract: Recent discoveries have led to the identification of a novel group of immune cells, the innate lymphoid cells (ILCs). The members of this group are divided into three subpopulations: ILC1s, ILC2s, and ILC3s. ILC2s produce Th2 cytokines, IL-4, IL-5, and IL-13, upon activation by epithelial cell-derived cytokines, lipid mediators (cysteinyl leukotrienes and prostaglandin D2), and TNF family member TL1A and promote structural and immune cell responses in the airways after antigen exposure. In addition, ILC2 funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 124 publications
(167 reference statements)
1
67
0
Order By: Relevance
“…5,6 ILC2 populations are found in several tissues, including the respiratory system, nose and skin, and there are strong correlations between the prevalence of ILC2s and the disease severity of asthma, chronic rhinosinusitis with nasal polyp and atopic dermatitis. 7,8 In our previous study, the prevalence of ILC2s was significantly increased in nasal polyps of patients with eosinophilic chronic rhinosinusitis, and it was positively correlated with the number of infiltrating eosinophils in nasal polyps. 8 However, the role of ILC2s in the pathophysiology of AR is not well understood.…”
Section: Introductionmentioning
confidence: 83%
“…5,6 ILC2 populations are found in several tissues, including the respiratory system, nose and skin, and there are strong correlations between the prevalence of ILC2s and the disease severity of asthma, chronic rhinosinusitis with nasal polyp and atopic dermatitis. 7,8 In our previous study, the prevalence of ILC2s was significantly increased in nasal polyps of patients with eosinophilic chronic rhinosinusitis, and it was positively correlated with the number of infiltrating eosinophils in nasal polyps. 8 However, the role of ILC2s in the pathophysiology of AR is not well understood.…”
Section: Introductionmentioning
confidence: 83%
“…ILC2s have been detected in samples from patients with a number of airway diseases and association studies link them to the pathologies observed in the human airways in response to exposure to environmental allergens and viruses. 94 It has been suggested that circulating human ILC2s are functionally immature and not actively primed for effector functions as they demonstrate low or absent expression of key effector molecules as well as receptors to IL-25 and IL-33, which allow ILC2s to respond to inflammatory signals in the lung. 66,67,76 This contrasts with ILC2s in the mouse, which constitutively express the key effector molecules that define ILC2s.…”
Section: Conclusion and Therapeutic Strategiesmentioning
confidence: 99%
“…In mice, TSLP is able to induce expression of costimulatory molecules on DCs [44]. In combination with IL-33 and IL-25, TSLP also participates in recruitment and proliferation of ILC2 in the lungs, leading to the release of pro-T H 2 molecules such as IL-4, IL-5, IL-9, IL-13, and amphiregulin [45], which was recently shown to perpetuate allergic inflammation [46]. TSLP can also modulate several functions of MCs [47], including the release of proinflammatory cytokines such as IL-6, TNF-α, and IL-1β, but not cell degranulation [41].…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%